SUSTAINABLE RECLAMATION PRACTICES FOR COPPER TAILINGS DAMS - PRIYANKA,; PRAMA ESTHER SOLOMAN,; PANKAJ KUMAR JAIN, (The Bioscan, 2025)
Mining generates billions of tons of tailings, significantly impacting the environment and society. The disposal of tailings poses significant risks to soil, water, and air quality, making effective treatment crucial for our environment. Adopting sustainable reclamation technologies is necessary to mitigate these negative effects and ensure environmental and economic security. These technologies include chemical stabilization, physical stabilization, biological reclamation, and integrated approaches. The extensive mining of tailings has resulted in considerable environmental and socioeconomic consequences. Addressing these issues requires effective treatment strategies that prioritize sustainable reclamation methods. This review highlights the importance of utilizing advanced technologies, continuous monitoring, community involvement, and robust policy frameworks. Future research should explore innovative cleanup technologies, integrate circular economy principles, and enhance resilience to climate change. These sustainable reclamation strategies offer the potential to mitigate environmental damage, support resource recovery, and improve the quality of life of affected communities.